Transformational Leadership and Organizational Commitments to Performance of State Civilians in the Local Government of East Luwu District - Sismiati Sismiati; Syarifuddin Sulaiman; Yudi Mochamad (Yayasan Ahmar Cendekia Indonesia, 2022)
This study aims to determine and analyze the effect of transformational leadership and organizational commitment on the performance of the state civil apparatus in the East Luwu Regency. This type of research is explanatory research that explains the effect of the independent variables on the dependent variable. This paper uses a quantitative approach in the form of statistical results to test the research hypothesis. This research was conducted in Luwu Raya Regency. The population in this study were all state civil servants in the local government of East Luwu Regency as many as 7,682 people. Determination of the number of samples using the Slovin approach, resulting in a total sample of 100 people. Sampling using an accidental sampling method. The analytical technique used in this research is multiple linear regression analysis. The results showed that simultaneously all independent variables (transformational leadership and organizational commitment) had a positive and significant effect on the performance of the state civil apparatus. The transformational leadership has a dominant effect on the performance of the state civil apparatus compared to the organizational commitment variable.